8 practice tests for reading and math, grade 3 - Priestley, Michael (New York : Scholastic, 2002)
Contains eight practice tests for reading and mathematics designed to help students in grade three prepare for standardized tests.
"Grade 3"--Cover.
"Great practice for the MAT, CTBS TerraNova, CAT, Stanford, and more!"--Cover.
Professional
Keywords: Mathematics -- Study and teaching; Reading; Teaching -- Aids and devices; Mathematics -- Study and teaching; Reading; Teaching -- Aids and devices